GAMBARAN STATUS NUTRISI PADA IBU PRIMIGRAVIDA DI PUSKESMAS RAWAT INAP SIDOMULYO KECAMATAN TAMPAN KOTA PEKANBARU - Nur Liana Hasibuan; Hellena Deli; Raja Fitrina Lestari (Jurnal Ilmu Keperawatan, 2018)
SEKOLAH TINGGI ILMU KESEHATAN HANG TUAH PEKANBARU PROGRAM STUDI ILMU KEPERAWATAN Undergraduate thesis, September 2017 Nurliana Hasibuan Description Of Nutrition Status On Primigravida Mother In Puskesmas Interest Of Sidomulyo Tampan District Of Pekanbaru City xvii+ 44 pages + 12 tables + 2 schemes + 32 attachments ABSTRACT Pregnancy is a condition in wich a woman has a growing fetus inside her body. This mother is in need of good nutrition for fetaldevloment. This study aims determine the description of nutritional status in primigravida mothers in Puskesmas Inpantient Sidomulyo District Tampan. Sampling technique using quota sampling. Data analysis to see frequency distribution and percentage of each variable. The results of this study indicate the distribution of nutrients in both primigravida mothers amounted to 41 respondents. In study the nutrition in primigravida mother that is in puskesmas of inpatient of sidomulyo subdistrict of tampan is still within normal limits this is in accordance with has been observed. Primigravida mother have to consult more often to health center, hospital and clinic, to know the health of the mother and fetus and about the nutrient that will consumed during pregnancy. Bibliography : 39 references (2004-2016) Keywords : Nutritional, Primigravida, Nutrional Status